Do wild ungulates utilize at-grade fauna passages as effectively as fauna overpasses or underpasses? - Elfström, Marcus; Olsson, Mattias (Frontiers in Conservation Science, 2025)
At-grade fauna passages are much less resources demanding to construct compared to wildlife overpasses or underpasses at infrastructure barriers. Because smaller and intermediate-sized roads are much more common than major roads in most landscapes, at-grade passages have a high potential for cost-efficient barrier mitigation for wildlife. However, at-grade passages have besides risk for vehicle collision involvement, a higher disturbance potential, compared to most over- and underpasses, considering foremost its multiuse with vehicle traffic. We tested if the crossing probability in common Scandinavian ungulates; wildboar (Sus scrofa), roedeer (Capreolus capreolus) and fallow deer (Dama dama), was impacted due to different types of crossing structure, while accounting for availability to alternative crossing sites and environmental factors. We found no differences in crossing probability in wild boar (851 visits), roedeer (1,556 visits) and fallow deer (941 visits) when comparing wildlife visits at 4 at-grade fauna passages and the combined result from 8 wildlife-designed over-/underpasses. This indicates that fauna passage at-grade (with average daily traffic volume of 3,000–8,000) can show similar functionality, in terms of comparable proportions of usage out of all visits, compared to wildlife designed overpasses or underpasses. In addition, when separating among over-, underpasses and at-grade passages, we found no differences in crossing probability in roe deer and fallow deer. Wildboar showed no difference in crossing probability between overpass and at-grade passage, but higher crossing probability at underpass than at-grade. This suggests that establishing several wildlife passages at-grade instead of only a few over- or underpasses designed for wildlife at different grade may be an alternative to reduce infrastructure barriers also along fenced intermediate-sized roads.